ANALISIS KETERLAKSANAAN PRAKTIKUM PEMBELAJARAN BIOLOGI KELAS XI DAN KELENGKAPAN FASILITAS LABORATORIUM DI SMA NEGERI 1 GOWA - Nurul Aisyah Syachrul, Wulandari; Pagarra, Halifah; Dwi Putri Ulan Sari Patongai, Dian (Universitas Cokroaminoto Palopo, 2025)
This study aims to determine the implementation of biology learning practicums in grade XI and to determine the completeness of biology laboratory equipment and materials at SMA Negeri 1 Gowa. This study is a descriptive study with a mixed methods approach using quantitative and qualitative methods. The subjects of this study were SMA Negeri 1 Gowa, including biology teachers and several students. Data collection techniques were carried out using a questionnaire containing a list of practical lessons in accordance with the learning outcomes in the independent curriculum and a checklist containing a list of laboratory facilities in accordance with the standards of Permendiknas No. 24 of 2007. The results of the study show that the average implementation of biology practicums at SMA Negeri 1 Gowa is 62.5%, which means that the implementation of biology practicums at SMA Negeri 1 Gowa is in the inadequate category. Meanwhile, the completeness of laboratory facilities obtained a score of 70%, which is in the complete category.